TINGKAT PENGETAHUAN DAN PERILAKU IBU TENTANG PENCEGAHAN INFEKSI SALURAN NAPAS ATAS (ISPA) PADA BALITA DI DESA DORUME - Sero, Renita Laurencia; Fitria, Pipit Nur (STIKES Suaka Insan, 2024)
Acute Respiratory Tract Infection (ARI) is the leading cause of morbidity among children under five in developing countries, including Indonesia. The high incidence of ARI in children under five is influenced by factors such as knowledge, age, occupation, and maternal behavior related to ARI. Maternal knowledge is expected to influence ARI prevention behavior in toddlers. This descriptive quantitative study involves 88 respondents, with a total sampling. The results showed that the majority of mothers in Dorume Village had poor knowledge (62%) and poor behavior (66%) related to ARI prevention in children under five. Only about 38% of mothers had good knowledge, while good behavior was seen in 34% of respondents. In conclusion, mothers in Dorume Village tend to have inadequate knowledge and behavior in preventing ARI in children under five. There is a need for counseling and education efforts to improve mothers' knowledge and behavior related to children's health, especially in preventing ARI. Keywords: Knowledge, Behavior, ARI